Evaluation of Current Industry Practices for Maintaining Tomato Dump Tank Water Quality during Packinghouse Operations. Issue 6 (3rd January 2014) - Zhou, Bin; Luo, Yaguang; Turner, Ellen R.; Wang, Qin; Schneider, Keith R.
Abstract Maintenance of adequate sanitizer levels in tomato dump tanks is critical to preventing pathogen survival and transfer, and internalization in the fruit. However, the rapid accumulation of organic matter in dump tanks can cause a significant decline in sanitizer concentration, thus leaving wash solutions vulnerable to becoming a reservoir for pathogens. This study investigated the dynamic changes in wash water quality and sanitizer concentration during routine operations of three medium to large tomato packinghouses in Florida in 2010 and 2011. Overall, water quality declined continuously during packinghouse operations, as exhibited by significant increases in chemical oxygen demand and turbidity. Free chlorine concentration, oxidation reduction potential and pH fluctuated largely as a consequence of periodic addition of sodium hypochlorite and citric acid, and the rapid loss of free chlorine caused by organic matter. Although the packinghouses differed significantly in system configuration, operation and chlorine dosing rates, at least 25 mg/L of free chlorine concentrations were maintained in all of the dump tanks surveyed. Practical Applications Wash water quality and sanitizer strength are important factors influencing food safety of tomatoes washed in packinghouses. Soil, debris and juices from damaged fruits entering dump tanks along with tomatoes can cause water quality and sanitizer strength to decline dramatically, leaving wash solutions vulnerable to the growth of harmful bacteria. Maintenance of adequate sanitizer levels in tomato dump tanks is critical to reducing pathogen survival, transmission and incidence of internalization in the fruit. The researchers surveyed the water quality and sanitizer concentrations during routine operations of three major tomato packinghouses in Florida in 2010 and 2011. The results are useful for the regulatory agency and tomato industry in developing packinghouse handling guidelines to maintain the quality and food safety of tomatoes.